3D printing in oral and maxillofacial surgery: a nationwide survey among university and non-university hospitals and private practices in Germany - Pabst, Andreas; Goetze, Elisabeth; Thiem, Daniel G. E.; Bartella, Alexander K.; Seifert, Lukas; Beiglboeck, Fabian M.; Kroeplin, Juliane; Hoffmann, Juergen; Zeller, Alexander-N. (Clinical Oral Investigations, 2021)
Objectives: Oral and maxillofacial surgery (OMFS) has undergone pioneering progress through the development of three-dimensional (3D) printing technologies. The aim of this study was to evaluate the use of 3D printing at OMFS university and non-university hospitals and private practices in Germany. Materials and methods: For explorative assessment, a dynamic online questionnaire containing 10–22 questions about the current use of 3D printing and the reasons behind it was sent to OMFS university and non-university hospitals and private practices in Germany by the study group from the German Association of Oral and Maxillofacial Surgery (DGMKG). Results: In total, 156 participants responded from university (23 [14.7%]) and non-university hospitals (19 [12.2%]) and private practices without (85 [50.5%]) and with 29 (18.6%) inpatient treatment facility. Highest applications of 3D printing were in implantology (57%), microvascular bone reconstructions (25.6%), and orthognathics (21.1%). Among the participants, 37.8% reportedly were not using 3D printing. Among the hospitals and private practices, 21.1% had their own 3D printer, and 2.5% shared it with other departments. The major reason for not having a 3D printer was poor cost efficiency (37.6%). Possessing a 3D printer was motivated by independence from external providers (91.3%) and rapid template production (82.6%). The preferred printing methods were stereolithography (69.4 %) and filament printing (44.4%). Conclusions: OMFS 3D printing is established in Germany with a wide range of applications. Clinical relevance: The prevalence of 3D printing in hospitals and private practices is moderate. This may be enhanced by future innovations including improved cost efficiency.
CRIS-Team Scopus Importer:2021-07-30
Keywords: 3D printing; Model; Patient-specific implants; Stereolithography; Surgical guides

An update on the current training situation of German interns in oral and maxillofacial surgery at special times in 2021 - Pabst, Andreas; Goetze, Elisabeth; Thiem, Daniel G.E.; Bartella, Alexander K.; Seifert, Lukas; Beiglboeck, Fabian M.; Kröplin, Juliane; Hoffmann, Jürgen; Zeller, Alexander N. (Journal of Cranio-Maxillofacial Surgery, 2022)
The aim of this study was to evaluate the current state of training of German interns in oral and maxillofacial surgery (OMFS) under the influence of the COVID-19 pandemic in 2021. A previously tested questionnaire consisting of 53 questions was sent to interns in German OMFS (non-) university hospitals and private practices as an online survey. The questionnaire was adapted to current topics, such as the ongoing COVID-19 pandemic, aspects concerning nighttime and weekend services, overtime hours, surgical logbooks, benefits of academic degrees and support for scientific activities, part-time employment, parental leave and childcare. Next, results of questions from before the COVID-19 pandemic were re-evaluated. The COVID-19 pandemic influenced the clinical work (71.83%) and the current state of training (68.64%) in OMFS of most participants. Nighttime and weekend services are possible for employees in possession of only one degree (87.93% with a medical degree) in most hospitals. Not having one or both doctorate degrees was considered to be a disadvantage by 54.95%. In all, 42.11% of the participants attested to a positive influence of research on their training situation, and 50% reported financial or non-financial research support from the employer. Part-time employment was possible for 78.81% of the participants. The course of training was interrupted more often for women due to parental or maternity leave (10.53% of men and 30.95% of women). A total of 40.71% of the participants reported that childcare was available at the hospital, theoretically. The state of OMFS training in Germany can be referred to as positive. Current and future challenges are diverse, including aspects originating from the ongoing COVID-19 pandemic, gender aspects, reconciliation of family and work, and flexible working hours. Addressing these topics will ensure OMFS training at the highest surgical level and further increase interns’ satisfaction, preserving the specialty's popularity and reception.
CRIS-Team Scopus Importer:2022-03-18
Keywords: COVID-19 pandemic; Intern; Oral and maxillofacial surgery; Survey; Training

A survey regarding the organizational aspects and quality systems of in-house 3D printing in oral and maxillofacial surgery in Germany - Zeller, Alexander-N; Goetze, Elisabeth; Thiem, Daniel G. E.; Bartella, Alexander K.; Seifert, Lukas; Beiglboeck, Fabian M.; Kroeplin, Juliane; Hoffmann, Jurgen; Pabst, Andreas (Oral and maxillofacial surgery, 2022)
Purpose The aim of the study was to get a cross-sectional overview of the current status of specific organizational procedures, quality control systems, and standard operating procedures for the use of three-dimensional (3D) printing to assist in-house workflow using additive manufacturing in oral and maxillofacial surgery (OMFS) in Germany. Methods An online questionnaire including dynamic components containing 16-29 questions regarding specific organizational aspects, process workflows, quality controls, documentation, and the respective backgrounds in 3D printing was sent to OMF surgeons in university and non-university hospitals as well as private practices with and without inpatient treatment facilities. Participants were recruited from a former study population regarding 3D printing; all participants owned a 3D printer and were registered with the German Association of Oral and Maxillofacial Surgery. Results Sixty-seven participants answered the questionnaires. Of those, 20 participants ran a 3D printer in-unit. Quality assurance measures were performed by 13 participants and underlying processes by 8 participants, respectively. Standard operating procedures regarding computer-aided design and manufacturing, post-processing, use, or storage of printed goods were non-existent in most printing units. Data segmentation as well as computer-aided design and manufacturing were conducted by a medical doctor in most cases (n = 19, n = 18, n = 8, respectively). Most participants (n = 8) stated that "medical device regulations did not have any influence yet, but an adaptation of the processes is planned for the future." Conclusion The findings demonstrated significant differences in 3D printing management in OMFS, especially concerning process workflows, quality control, and documentation. Considering the ever-increasing regulations for medical devices, there might be a necessity for standardized 3D printing recommendations and regulations in OMFS.
CRIS-Team WoS Importer:2022-09-02

Correction to: How is neck dissection performed in Oral and maxillofacial surgery? Results of a representative nationwide survey among university and non-university hospitals in Germany (Clinical Oral Investigations, (2021), 25, 5, (3007-3019), 10.1007/s00784-020-03622-9) - Pabst, Andreas; Thiem, Daniel G. E.; Goetze, Elisabeth; Bartella, Alexander K.; Neuhaus, Michael T.; Hoffmann, Juergen; Zeller, Alexander-N. (Clinical Oral Investigations, 2021)
During a routine check, the Open Access coordinator noticed that article https://doi.org/10.1007/s00784-020-03622-9 was published without OA, although the author choose Open Access. Additionally, the article was approved under DEAL on 08/10/2020. The original article has been corrected.
CRIS-Team Scopus Importer:2021-05-28

How is neck dissection performed in Oral and Maxillofacial Surgery? Results of a representative nationwide survey among university and non-university hospitals in Germany - Pabst, Andreas; Thiem, Daniel G.E.; Goetze, Elisabeth; Bartella, Alexander K.; Neuhaus, Michael T.; Hoffmann, Jürgen; Zeller, Alexander N. (Clinical Oral Investigations, 2021)
Introduction: Neck dissection (ND) is a surgical procedure addressing cervical lymph nodes and metastases in patients with oral squamous cell carcinoma (OSCC). The aim of this study was to analyze clinical decisions regarding indications and variations of ND in Oral and Maxillofacial Surgery (OMFS) in Germany. Material and methods: A nationwide survey of the German Association of Oral and Maxillofacial Surgery was performed using dynamic online questionnaires including 38 questions. Data about oncological centers, case numbers, and staging procedures were collected. Relevant aspects, such as inclusion of level IIb and levels IV and V to ND, uni- vs. bilateral ND, and the influence of extra-nodal extension (ENE) of metastases on extension of ND were evaluated. Results: Eighty-four OMFS of university and non-university hospitals participated in the study (responding rate 21.4%). Sixty-six (78.57%) stated to work at certified cancer centers and 53.57% of the hospitals treated between 50 and 100 OSCC cases per year. CT and/or MRI of the head and neck was performed in most of the staging procedures. Level IIb was included by 71 (93.42%) of the participants in selective ND. Levels IV and V were included by 53 (69.74%) in node-positive neck. In solitary ipsilateral metastases (ENE−), 49 participants (62.82%) stated to perform exclusively an ipsilateral ND and 40 (51.95%) stated to perform only an ipsilateral ND in ENE+. Conclusion: This study demonstrated a high rate of certified cancer centers in Germany showing differences regarding staging procedures, indications, and extension of ND, especially in increasingly complex cases. Clinical relevance: Clinical decisions regarding ND are dependent on case-individual aspects and must be decided individually.
CRIS-Team Scopus Importer:2021-04-09
Keywords: Lymph node; Metastases; Neck dissection; Oncology; Oral squamous cell carcinoma; Survey

Identification of cutaneous perforators for microvascular surgery using hyperspectral technique – A feasibility study on the antero-lateral thigh - Goetze, Elisabeth; Thiem, Daniel; Gielisch, Matthias W.; Kämmerer, Peer W. (Journal of Cranio-Maxillofacial Surgery, 2020)
Aim of the study was to compare perforator vessel location using color-coded Doppler ultrasound and hyperspectral imaging in the area of the antero-lateral thigh. In a cross-sectional case-control study, the bilateral antero-lateral thigh region was examined for perforator vessel location via color-coded Doppler ultrasound (control) and hyperspectral imaging (test). For hyperspectral imaging, all measurements were conducted without cooling (T0) and after 1 (T1), 2 (T2) and 3 min (T3) of cooling. Additionally, in the reperfusion period after cooling, hyperspectral imaging was conducted at 1, 2 and 3 min (T4/T5/T6). Results from color-coded Doppler ultrasound and hyperspectral imaging were matched at all time points (T0–T6). In total, 71/73 perforator vessel locations could be matched (sensitivity: 97%). Matching of color-coded Doppler ultrasound and hyperspectral imaging was significantly influenced by the cooling protocol and the highest matching values were seen at T3 (3 min cooling; 60 perforator vessels) and T4 (3 min cooling & 1 min reperfusion; 62 perforator vessels) without significant differences (sensitivity 98%; p = 0.9). There were significant differences between T4 and T0, T1 (both p < 0.001), T5 (p = 0.045) and T6 (p = 0.012). For clinical proof of concept, a patient case using a free antero-lateral thigh flap for reconstruction of a facial defect after perforator vessel identification via color-coded Doppler ultrasound and hyperspectral imaging (3 min cooling & 1 min reperfusion) was carried out successfully. In conclusion, hyperspectral imaging potentially offers an additional opportunity for non-invasive, user-independent perforator-site assessment if prior cooling of the site is conducted.
CRIS-Team Scopus Importer:2020-11-20
Keywords: Cutaneous perforator; Flap assessment; Hyperspectral imaging; Microvascular surgery; Perforator flap

Microvascular reconstructions in oral and maxillofacial surgery — Results of a survey among oral and maxillofacial surgeons in Germany, Austria, and Switzerland - Pabst, Andreas; Zeller, Alexander N.; Raguse, Jan Dirk; Hoffmann, Jürgen; Goetze, Elisabeth (Journal of Cranio-Maxillofacial Surgery, 2023)
This study aimed to evaluate the use of microvascular free flaps (MFF) in oral and maxillofacial surgery (OMFS) in Germany, Austria, and Switzerland. A dynamic online questionnaire, using 42–46 questions, was sent to OMF surgeons based in hospitals in Germany, Austria, and Switzerland. The questionnaire was evaluated internally and externally. Aside from general information, data were collected on organizational aspects, approaches, MFF types and frequency, presurgical planning, intraoperative procedures, perioperative medications, flap monitoring, and patient management. Participants mostly performed 30–40 MFF each year (11/53). Most stated that the COVID-19 pandemic did influence MFF frequency (25/53) to varying extents. Radial forearm flap was most frequently used (37/53), followed by ALT (5/53), and fibula flap (5/53). Primary reconstruction was performed by most participants (35/48). Irradiated bony transplants were mostly used for implant placement after 12 months (23/48). Most participants (38/48) used reconstruction plates, followed by miniplates (36/48), PSI reconstruction (31/48), and PSI miniplates (10/48). Regarding the postoperative use of anticoagulants, low-molecular-weight (37/48) and unfractioned heparins (15/48) were widely used, most often for 3–7 days (26/48). Clinical evaluation was mostly preferred for flap monitoring (47/48), usually every 2 h (34/48), for at least 48 h (19/48). Strong heterogeneity in MFF reconstructions in OMFS was found, especially regarding the timepoints of reconstruction, types of osteosynthesis, and postoperative MFF management. These findings provide the chance to further compare the different treatment algorithms regarding relevant MFF aspects, such as postoperative management. This could create evidence-based treatment algorithms that will further improve the clinical outcomes in MFF reconstructions.
CRIS-Team Scopus Importer:2023-03-24
Keywords: DÖSAK; Microvascular free flap; Oral and maxillofacial surgery; Reconstruction; Survey

Neck dissection in oral and maxillofacial surgery Results of a German national survey among OMF surgeons - Pabst, Andreas; Goetze, Elisabeth; Zeller, Alexander-N (Der MKG-Chirurg, 2021)
CRIS-Team WoS Importer:2021-08-27

Performance of different osteosynthesis materials in microvascular fibula free flap reconstruction - Nobis, Christopher-Philipp; Lutz, Rainer; Weber, Margarete; Preidl, Raimund; Goetze, Elisabeth; Frohwitter, Gesche; Kesting, Marco Rainer (British Journal of Oral and Maxillofacial Surgery, 2022)
Purpose: Fibula free flap (FFF) is the main reconstructive choice for large mandibular defects. Recent improvements were made regarding planning and surgical procedure, but choice of osteosynthesis material (OSM) for segment-fixation remains controversial. Materials and methods: A retrospective cohort study obtained clinical and radiological data from FFF-patients. Data was screened for OSM, surgical procedure and complications as OSM fractures, loosening, exposure, or insufficient osseous consolidation. Results: 80 patients with FFF were included. Planning was CAD/CAM (n=29), Recon Guide (n=26) or without planning (n=25). OSM was 2.0mm-miniplates in standard (n=26), preformed (n=6), CAD/CAM (n=14) or ReconGuide (n=23) variation and 2.3mm-reconstruction-plates in standard (n=5) or CAD/CAM (n=6) variation. Complications were observed in 21 cases, fractures in 10 times overall, but with low rates for preformed (n=1), ReconGuide (n=3) and none for CAD/CAM. Analysis detected significant correlations between used OSM and plate exposure (p = .000), but none regarding fracture (p = .275), loosening (p = .714) or insufficient osseous consolidation (p = .208). No correlations were observed between complications and OSM (p = .609) or diagnosis (p = .716). Conclusion: Fixation of FFF segments for reconstruction is possible with various OSM providing good clinical outcome. No significant differences were detected regarding prevention of complications by any osteosynthesis material (miniplate vs. macroplate). Although no differences were detected, miniplate usage is advocated whenever clinically reasonable, due to more facile reintervention possibilities and reduced implanted foreign material. Nevertheless, decision for ideal OSM must remain patient-specific and cannot be generalized.
CRIS-Team Scopus Importer:2022-04-08
Keywords: CAD/CAM; complications; fibula free flap; miniplate; osteosynthesis; ReconGuide